Penyebab Mortalitas Lansia Selama Masa Perawatan Rumah Sakit COVID-19: A Systematic Review - Agnes Dewi Astuti; Bernadetta Germia Aridamayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: The first case of COVID-19 was first reported in China in December 2019 and spread rapidly to various countries. On July 13, 2020, COVID-19 was officially declared a world pandemic by the WHO. COVID19 affects more than 210 countries in the world and kills millions of people with 21% of deaths occurring in the elderly. Objective: To describe the risk factors and causes of elderly mortality during the period of treatment or quarantine in the hospital by COVID-19. Methods: The database used as a reference, among others, is Scopus, PubMed and Science Direct, which is limited to publications in the last 2 years from 2020 to 2021, full text articles selected in English. Meanwhile, the keywords used in the article search are "COVID-19" AND "elderly clinical of SARS-CoV-2" AND "pandemic mortality". This systematic review used 5 articles that met the inclusion criteria. Results: Risk factors or causes of elderly mortality during COVID-19 hospital treatment include chormobid such as dementia, respiratory disorders such as asthma, diabetes mellitus, chronic kidney disease and hypertension. Conclusions: Various non-communicable diseases that accompany COVID-19 will be a risk factor and even a leading cause of death in the elderly during hospital treatment.Keywords: COVID-19; elderly clinical of SARS-CoV-2; pandemic mortalityABSTRAKLatar belakang: Kasus pertama COVID-19 pertama kali dilaporkan di China pada Desember 2019 dan menyebar dengan cepat ke berbagai negara. Pada 13 Juli 2020, COVID-19 resmi diumumkan sebagai pandemik dunia oleh WHO. COVID-19 mempengaruhi lebih dari 210 negara yang ada di dunia dan membunuh jutaan jiwa dengan 21% kasus kematian paling banyak terjadi pada lansia. Tujuan: Untuk menjabarkan faktor risiko maupun penyebab kejadian mortalitas lansia selama masa perawatan atau karantina di rumah sakit oleh COVID-19. Metode: Database yang digunakan sebagai referensi antara lain adalah Scopus, PubMed dan Science Direct yang dibatasi dalam publikasi 2 tahun terakhir terhitung sejak dari 2020 hingga 2021, full text article yang dipilih menggunakan bahasa Inggris. Sedangkan, kata kunci yang digunakan pada pencarian artikel adalah “COVID-19” AND “elderly clinical of SARS-CoV-2” AND “pandemic mortality”. Systematic review ini menggunakan 5 artikel yang sesuai dengan kriteria inklusi. Hasil: Faktor Risiko ataupun penyebab mortalitas lansia selama masa perawatan COVID-19 dirumah sakit antara lain adalah kormobid seperti demensia, gangguan pernapasa seperti asma, diabetes melitus, penyakit ginjal kronis dan hipertensi. Simpulan: Berbagai macam penyakit tidak menular yang disertai dengan COVID-19 akan menjadi faktor risiko bahkan penyebab utama kematian pada lansia selama masa perawatan di rumah sakit.Kata kunci: COVID-19; elderly clinical of SARS-CoV-2; pandemic mortality